Geopolitical Dynamics in South Asia: A Comparative Study of Chinese and Indian Interests in the Sovereignty and Politics of Nepal - Pokharel, Arjun Prasad (Academia Research Journal, 2024)
Nepal, a landlocked nation strategically positioned between China and India, plays a pivotal role in South Asia’s geopolitics. Historically, Nepal has preserved its sovereignty despite external pressures, particularly from its powerful neighbors. In the 21st century, the competition between China and India has intensified, with both nations pursuing their strategic, economic, and security interests in Nepal. China prioritizes stability, adherence to the One-China policy, and economic integration, while India emphasizes historical ties and strategic involvement in Nepal’s politics. This study investigates the geopolitical dynamics influencing Nepal, focusing on the period after 2005, when Nepal transitioned from a monarchy to a federal democratic republic. The study aims to explore the historical evolution of Nepal’s political landscape, analyze the motivations driving Chinese and Indian interests, and evaluate their impact on Nepal’s sovereignty and development. Adopting a qualitative approach, the research utilizes secondary data from scholarly publications, reports, and expert interviews to provide a comprehensive analysis. The findings reveal divergent strategies: China adopts a non-interference policy emphasizing economic collaboration, while India’s active political involvement has often led to disputes. The conclusion highlights Nepal’s critical need to balance its foreign relations, safeguard sovereignty, and leverage its strategic position for stability and sustainable growth.